OFF-LABEL PEDIATRIC DRUG USE IN INDONESIA : A SYSTEMATIC REVIEW - Dewi Latifatul Ilma; Nialiana Endah Endriastuti (Universitas Muhammadiyah Magelang, 2020)
The phenomenon of off-label drug use has been widely observed in the pediatric population, including in Indonesia. The major concern arising from the prevalence of off-label drug use is the increased risk of adverse drug reactions. We performed a systematic review to describe and provide insight into off-label pediatric drug use in Indonesia. The articles published using English and Indonesian language was systematically searched in five electronic databases, including Pubmed, Scopus, Google Scholar, Garuda, and Neliti. Key terms used for the search were as follows: